Modeling the Influence of Deposition Parameters on the Crystalline Degree in the Simulation of Polycrystalline Silicon - Santonen, Mikael; Lahti, Antti; Srivastava, Divya; Jahanshah Rad, Zahra; Miettinen, Mikko; Ebrahimzadeh, Masoud; Laaksonen, Johanna; Laukkanen, Pekka; Punkkinen, Marko; Kokko, Kalevi; Kuronen, Antti; Parkkinen, Katja; et al. (WILEY-V C H VERLAG GMBH, 2025)
Polycrystalline silicon (poly-Si) has been and still is a pivotal material, particularly in the electronics and solar energy industries. Controlling crystallization is one of the challenges, e.g., in producing poly-Si films for radio frequency applications. Since film growth by deposition is a random process, producing a specific grain size distribution for poly-Si is challenging. By combining molecular dynamics simulation data with surface diffusion physics, novel transparent models are constructed that shed light on the physics behind the deposition of poly-Si thin films and assist the selection of simulation parameters. Both probabilistic and geometric approaches are used to find relevant simulation parameters and their bounds to describe the complex grain-grain boundary interactions in the growth of poly-Si thin films. Poly-Si growth simulations provide valuable information to better understand the features of optimal growth conditions. The constructed parameterized deposition model is fitted to the simulation data. In addition to further refining the simulation of customized poly-Si films, the presented modeling concept can also be used more generally in the analysis of physical vapor deposition.